Inflammatory markers in outpatients with schizophrenia diagnosis in regular use of clozapine: a cross-sectional study - Cordova, Victor Hugo Schaly; Teixeira, Amelia Dias; Anzolin, Ana Paula; Moschetta, Roberta; Belmonte-de-Abreu, Paulo Silva (Frontiers in Psychiatry, 2023)
It is known that inflammation worsen the course of schizophrenia and induce high clozapine serum levels. However, no study evaluated this change in function of clozapine daily dose in schizophrenia. We assessed the correlation between inflammation and severity symptoms in patients with schizophrenia that take and do not take clozapine. We also assessed the correlation between clozapine daily dose and inflammatory markers to patients who take this drug. Patients were recruited from Schizophrenia Ambulatory and Psychosocial Care Center of Hospital de Clínicas de Porto Alegre and from an association of relatives of patients with schizophrenia. Exam results, and other important clinical exam were assessed in patients record or patients were asked to show their exam in the case of outpatients. We included 104 patients, 90 clozapine users and 14 non-clozapine users. We calculate the systemic inflammatory markers (neutrophil-lymphocyte ratio (NLR), immune-inflammatory systemic index (ISI) and the psychopathology severity by the Brief Psychiatric Rating Scaled anchored (BPRS-a). These variables were compared between clozapine users and non-clozapine users. It was used mean/median test according to data distributing, with study factor (ISI, NLR), the clinical outcome: severity of symptomatology (BPRS score), and clozapine daily dose as adjustment factor. Clozapine users exhibited a significantly higher neutrophil count (mean ± SD: 5.03 ± 2.07) compared to non-clozapine users (mean ± SD: 3.48 ± 1.27; p = 0.031). After controlling for comorbidity, other parameters also showed significant differences. These findings are consistent with previous studies that have demonstrated an inflammatory response following the administration of clozapine.